2015
DOI: 10.1007/s10461-015-1214-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Drug and Alcohol Use Patterns and Sexual Risk in a Sample of African American Men Who Have Sex with Men

Abstract: Men who have sex with men (MSM) are the largest risk group in the US HIV epidemic and African American MSM (AA MSM) are disproportionately affected. Substance-abusing sexual minorities warrant attention as they are at elevated risk for HIV, yet are not a homogeneous risk group. The purpose of this study was to use latent class analysis to identify patterns of drug and alcohol use in a sample of 359 AA MSM and examine associations with sexual risk. Three classes were identified: Individuals who used multiple su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Another finding from our study that individuals who were both frequent crack/cocaine users and binge drinkers had a greater likelihood of recent incarceration (previous 3 months) is consistent with previous reports documenting poly-drug users have a greater risk for experiencing incarceration (Tobin et al, 2015). Often individuals who use substances are at increased risk for incarceration and a significant proportion of substance using MSM are involved with the criminal justice system.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another finding from our study that individuals who were both frequent crack/cocaine users and binge drinkers had a greater likelihood of recent incarceration (previous 3 months) is consistent with previous reports documenting poly-drug users have a greater risk for experiencing incarceration (Tobin et al, 2015). Often individuals who use substances are at increased risk for incarceration and a significant proportion of substance using MSM are involved with the criminal justice system.…”
Section: Discussionsupporting
confidence: 93%
“…However, MSM subpopulations are not homogenous and often exhibit different substance-use related risk profiles (Newcomb, Ryan, Greene, et al, 2014). A recognition that different patterns of substance use among MSM populations may be associated with poor health or substance use treatment related outcomes is important in order to better tailor risk-reduction and substance use treatment related interventions (Tobin, Yang, King, et al, 2015). Thus, understanding how specific types of risk behaviors interact to place substance-using MSM populations, including those with co-occurring mental health disorders, at potentially greater overall risk for HIV infection and transmission can guide the development of intervention frameworks addressing multiple risk behaviors for these populations.…”
mentioning
confidence: 99%
“…This result corroborates the findings of a recent review (2) and of most studies of this kind in the world. (7,(10)(11)(12)(13) Mobile app use by MSM is a practical and efficient way to establish sexual partnerships quicker than conventional methods. Establishing partnerships through apps allows MSM to select partners according to their preferences and change their profile, which provides users with a different experience for expressing sexuality, (14) especially younger individuals, (15) one reason that explains the growing popularity of these apps.…”
Section: Discussionmentioning
confidence: 99%
“…Two analyses in Malaysian MSM (Lim et al, 2015) and African-American MSM (Tobin et al, 2016) each identified three classes: one with low substance use, one with low-threshold drug use and one with polydrug use. We were able to distinguish more specifically between different types of drug use in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other latent class-based approaches to understanding typologies of substance use have drawn primarily from the US context (McCarty-Caplan, Jantz, & Swartz, 2014;Tobin, Yang, King, Latkin, & Curriero, 2016;Yu, Wall, Chiasson, & Hirshfield, 2014). Thus, whether these drugs form a coherent pattern of use, or whether they are part of broader patterns of drug use,…”
Section: Introductionmentioning
confidence: 99%